MICROVASCULAR ANGINA IS ASSOCIATED WITH SYSTEMIC DYSFUNCTION OF PERIPHERAL RESISTANCE ARTERIES. (April 2021) - Michielon, Alberto; Lanza, Oreste; Ingrasciotta, Gesssica; Ferrera, Armando; Cesario, Vincenzo; Marino, Gaetano; Ruscio, Eleonora; Filice, Monica; De Vita, Antonio; Crea, Filippo; Volpe, Massimo; Lanza, Gaetano A.; et al.
Abstract : Objective: Microvascular angina (MVA) is characterized by functional and structural alterations of resistance coronary arteries without any significant alterations of epicardial coronary arteries. Whether MVA patients present also dysfunction of peripheral resistance arteries is still a matter of debate. We sought to evaluate whether MVA is associated with parameters of systemic microvascular dysfunction. Design and method: Thirteen patients with MVA and 13 healthy control subjects were enrolled in this study. The diagnosis of MVA was based on the presence of typical symptoms of ischemic heart disease, evidence of myocardial ischemia on exercise stress testing and normal epicardial coronary arteries at angiography. Parameters of peripheral microvascualar alterations, arterial stiffness (Pulse Wave Velocity, PWV), and central blood pressure (cBP) and Subendocardial Viability Ratio (SEVR, and index of subendocardial microvascular dysfunction), were evaluated by applanation tonometry. Results: Patients and controls were similar with respect to metabolic parameters, BMI, and renal function. MVA patients were on therapy with beta-blockers (50%), calcium channel blockers (37%), nitrates (12%), renin-angiotensin-blockers (44%), and statins (25%). MVA patients were slightly older than controls (63.6 ± 1.9 vs 53.1 ± 2.0 years, p < 0.05). Albeit in the normal range, peripheral (pSBP) and central (cSBP) systolic BP were significantly higher in MVA patients as compared to controls (pSBP:134.3 ± 2.9 vs 118.5 ± 3.5 mmHg, p < 0.002; and cSBP:124.8 ± 2.9 vs 109.7 ± 2.9 mmHg, p < 0.001). Diastolic BP was similarly preserved in both groups. SEVR, an index of subendocardial microvascular dysfunction, was lower in MVA patients as compared to controls (139.7 ± 4.1 vs 160.4 ± 8.5 %, p < 0.05). Augmentation index (AI), reflected (RPH), and forward (FPH) pulse height, all parameters of peripheral microvascular dysfunction, were also altered in MVA patients as compared to controls (AI:29.0 ± 1.0 vs 19.9 ± 2.4%, p < 0.003; RPH:22.3 ± 1.4 vs 15.3 ± 0.9 mmHg, p < 0.001; FPH:31.0 ± 1.4 vs 24.2 ± 1.4 mmHg p < 0.005). The index of aortic stiffness PWV was similar in both groups (7.20 ± 07 vs 6.6 ± 0.2 m/sec, NS). Conclusions: Patients with MVA on optimal anti-schemic therapy exhibit alterations of parameters of both subendocardial and peripheral microvascular dysfunction, suggesting that coronary microvascular dysfunction is part of a more generalized disorder also involving peripheral resistance arteries.